Measuring the transformative utopian impulse for planetary health in the age of the Anthropocene: a multi-study scale development and validation. Issue 3 (March 2022) - Basso, Frédéric; Krpan, Dario
Summary: Background: Transformative utopian impulse for planetary health is people's propensity to have thoughts and engage in actions of which the purpose is to transform the current society into a better one in the future by addressing existing global issues. We aimed to develop a well-validated scale that can measure the transformative utopian impulse for planetary health and uncover its role in societal transformation. Methods: We developed a scale to measure the transformative utopian impulse for planetary health across 11 studies with 6248 participants from the USA (from the MTurk database) and the UK (from the Prolifico.co database). Participants were eligible take part in the studies if they completed the consent form. Participants who did not pass the seriousness check or did not accurately answer all instructed response items were excluded from statistical analyses. We used exploratory factor analyses (EFA) and confirmatory factor analyses (CFA) to determine the factor structure of the Transformative Utopian Impulse for Planetary Health Scale (TUIPHS). Then we analysed the TUIPHS' nomological network (ie, the relationships between TUIPHS and various constructs ranging from personality traits and values to economic, social, and political attitudes and beliefs). We then examined the scale's incremental predictive validity by testing whether it predicts various attitudes and behaviours relevant to social change beyond scales that measure competing constructs (this part of the study is registered at OSF Registries [https://osf.io/ztj2f ]). Finally, we examined the TUIPHS' longitudinal predictive validity by probing whether it predicts people's future support for social change. Findings: Data were collected between Oct 8, 2018, and July 6, 2020. We established that TUIPHS has a four-factor structure and can also be scored as a single general factor, indicating that it captures an overarching theoretical construct (ie, the transformative utopian impulse for planetary health). We then showed that the scale is related to various specific individual difference measures that capture diverse aspects of people's propensity to actively engage in thoughts and actions oriented toward the betterment of society. Moreover, TUIPHS predicted, above and beyond 20 competing scales highly correlated ( r ≥0·50) with it, a series of 19 self-reported behavioural and attitudinal constructs pertaining to social change. Finally, participants' past TUIPHS scores predicted their support, a few months later, for social movements that aim to build a more just and resilient society than in the current day. Interpretation: This research lays the groundwork for future theoretical and empirical research into the psychological and behavioural processes attached to the transformative utopian impulse for planetary health as a source of transformative social change toward a better way of being and living. Funding: The London School of Economics and Political Science.